FORMATION OF CREATIVE ABILITIES OF STUDENTS AT STUDY OF PEDAGOGICAL DISCIPLINES IN TECHNOLOGICAL FACULTIES - O.V. Rohozina (Academy of Cognitive and Natural Sciences, 2008)
In article opportunities of formation of creative abilities of students are shown during teaching pedagogical disciplines on technologists by the check faculty.